Xylazine-ketamine anaesthesia in snakes (Naja naja) and its reversal with atipamezole - Pratap, K; Amarpal, Amarpal; Kinjavdekar, P; Aithal, H P; Pawde, A M (The Indian Journal of Animal Sciences, 2011)
Five venomous snakes (Naja naja ) were anaesthetized by a combination of ketamine (40 mglkg body weight) and xylazine (OAmg/kg) given intramuscularly. The onset ofanaesthesia, duration, depth and recovery period were recorded up to 120 h. The anaesthetic effect ranged from tranquilization to deep surgical anaesthesia. The combination ofketamine and xylazine was found safe, non-toxic with no clinical side effects except the prolonged recovery (40-90 h), which was shortened to 4 h by injecting atipamezole @4 mg/kg body weight intramuscularly.